The Influence of Hip Joint Fitness, Eye-Foot Coordination and Confidence on Accuracy Shooting Football Aged-17 Athletes - Jufrianis; Vigi Indah Permatha Sari; Elfera Riski (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. This research aims to find out how much influence confidence and confidence have on accuracy shooting football. Materials and methods. Sample size of 23 people, U-17 athletes from the Pahlawan Football Club University. The research method used in this research is a survey method with non-test techniques. The analysis technique used is the path analysis approach (path analysis) with the research results there is a direct positive influence of hip joint flexibility on accuracyShooting in football games for U-17 FC Pahlawan University athletes, with a percentage of 20.00%. Results. There is a direct positive influence of Confidence on AccuracyShooting in football games for U-17 FC Pahlawan University athletes, with a percentage of 40.00%, Conclusions. It can be concluded that hip joint flexibility and self-confidence play an important role in accuracyshooting in a football game. thus accuracyshooting in the game of football can be maximized through increasing hip joint flexibility, eye-foot coordination and self-confidence.